Kuantitas dan Karakteristik Sampah Bahan Pangan : Studi Kasis Surabaya Selatan - Sabrinatus Amalia Gustannanda; Euis Nurul Hidayah; Aulia Ulfah Farahdiba (Yayasan Literasi Sains Indonesia, 2023)
Food loss can be defined as the reduction of food quantity at each stage of the food supply chain, particularly in the type of food consumed by humans. This study aims to directly measure the amount and composition of food waste in order to provide complete and detailed information, which can also be used as a reference in formulating policies or preventive actions. Measurement of the quantity and composition of waste refers to SNI 19-3964-1994 with a sampling process for seven consecutive days based on the EPA's